Penegakan Hukum Terhadap Notaris Pelaku Tindak Pidana Penggelapan Uang Pajak Bea Perolehan Hak Atas Tanah Dan Bangunan (Bphtb) - Yolanda, Moch Andre; Chandra, Tofik Yanuar; Ismed, Mohamad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Law enforcement against notaries involved in the embezzlement of Land and Building Rights Acquisition Duty (BPHTB) aims to uphold justice and maintain the integrity of the notary profession. Notaries involved in BPHTB embezzlement violate criminal law and the professional code of ethics, making them subject to criminal and administrative sanctions. The law enforcement process includes investigation, prosecution, and court decisions carried out in accordance with applicable laws and regulations to ensure legal certainty and protect the rights of the parties involved. The research method used is normative juridical research, employing a statutory approach, case approach, conceptual approach, and analytical approach, based on primary, secondary, and tertiary legal materials. The legal material collection technique involves identifying and inventorying positive legal rules, while the legal material analysis technique used is grammatical and systematic interpretation. The research findings indicate that regulations regarding notaries receiving entrusted BPHTB funds for payment to the state treasury are not clearly stipulated in existing laws or regulations. However, if a notary receives authorization from a client to pay the tax, they are responsible for the entrusted funds as an agreeing party, not as a notary. This creates legal bias because the notary changes their role to an agreeing party, potentially causing public concern due to unclear legal protection. Law enforcement against notaries who commit BPHTB tax embezzlement refers to Articles 372 to 376 of the Indonesian Criminal Code (KUHP) on embezzlement, as the Notary Position Law (UUJN) does not explicitly regulate such offenses. Sanctions include imprisonment and fines under the Criminal Code, as well as professional sanctions ranging from written warnings to dishonorable discharge or license revocation by the Minister under the UUJN